Integration E-Learning Tools in Teaching and Learning English Language: Literature Review - Alshahrani, Nada (Advances in Social Sciences Research Journal, 2023)
This paper as a literature reviews, its primary goal is to examine the effect of the employment of E-Learning tools technology in teaching and learning English language. The English language play an important and crucial role in education environment. As a result, it is an essential for students to acquire a good understanding in education environment. Using traditional style in delivering information to learners might not assist and expand their English skills. Integration new technology in teaching and learning English language is a good technique that can help learners to acquire information quickly. Hence, this research the impact of the adoption of e-learning tools in teaching and learning English language. Also, this paper will provide some recommendations and suggestions for the future work.